Analysis and implementation of National Security Agency suite B : elliptic-curve digital signature algorithm - Lei, Min. (2009)
Elliptic Curve Digital Signature Algorithm (ECDSA) is the elliptic curve analogue of the Digital Signature Algorithm. Standard Suite B defines methods for digital signature generation and verification for the protection of messages and data using the ECDSA. In addition, this ECDSA standard provides the criteria for the generation of public and private keys that are required by the algorithm and the procedural controls required for the secure use of the algorithm. This report documents the analysis and implementation of the function of Suitee B ECDSA digital signature algorithm for the protection of classified information up to the SECRET level.